Penitentiary policies and criminal gangs - Salla, Fernando; Dias, Camila Nunes; Silvestre, Giane (FCL-UNESP Laboratório Editorial, 2012)
The article discusses the initiatives taken in the prison system in São Paulo in order to curb the activities of organized groups of prisoners, especially the PCC. The predominance of short-term administrative measures – usually in response to an event of great public impact – reflects the absence of comprehensive planning and action in this sector. We discuss two administrative measures designed to dismantle criminal groups: the dispersion of prisons within the state and the creation of units with different security and discipline regimes – for regular regimes as well as for the RDD. Besides the lack of public policies, the strengthening of administrative actions shall protect the sovereignty of the prison administration decisions on classificatory and punitive issues, which prevents the execution of criminal judiciary authority. The main consequence of this perverse state of affairs is the absolute ineffectiveness of prison administration in the weakening of criminal gangs.